Homozygous missense mutation in UQCRC2 associated with severe encephalomyopathy, mitochondrial complex III assembly defect and activation of mitochondrial protein quality control - Burska, Daniela; Stiburek, Lukas; Krizova, Jana; Vanisova, Marie; Martinek, Vaclav; Sladkova, Jana; Zamecnik, Josef; Honzik, Tomas; Zeman, Jiri; Hansikova, Hana; Tesarova, Marketa (Biochimica et biophysica acta. Molecular basis of disease, 2021)
The mitochondrial respiratory chain (MRC) complex III (CIII) associates with complexes I and IV (CI and CIV) into supercomplexes. We identified a novel homozygous missense mutation (c.665G>C; p.Gly222Ala) in UQCRC2 coding for structural subunit Core 2 in a patient with severe encephalomyopathy. The structural data suggest that the Gly222Ala exchange might result in an altered spatial arrangement in part of the UQCRC2 subunit, which could impact specific protein-protein interactions. Accordingly, we have found decreased levels of CIII and accumulation of CIII-specific subassemblies comprising MT-CYB, UQCRB, UQCRQ, UQCR10 and CYC1 subunits, but devoid of UQCRC1, UQCRC2, and UQCRFS1 in the patient's fibroblasts. The lack of UQCRC1 subunit-containing subassemblies could result from an impaired interaction with mutant UQCRC2Gly222Ala and subsequent degradation of both subunits by mitochondrial proteases. Indeed, we show an elevated amount of matrix CLPP protease, suggesting the activation of the mitochondrial protein quality control machinery in UQCRC2Gly222Ala fibroblasts. In line with growing evidence, we observed a rate-limiting character of CIII availability for the supercomplex formation, accompanied by a diminished amount of CI. Furthermore, we found impaired electron flux between CI and CIII in skeletal muscle and fibroblasts of the UQCRC2Gly222Ala patient. The ectopic expression of wild-type UQCRC2 in patient cells rescued maximal respiration rate, demonstrating the deleterious effect of the mutation on MRC. Our study expands the phenotypic spectrum of human disease caused by CIII Core protein deficiency, provides insight into the assembly pathway of human CIII, and supports the requirement of assembled CIII for a proper accumulation of CI.
Keywords: Mitochondria; Caseinolytic mitochondrial matrix peptidase proteolytic subunit (CLPP); Humans; Respiratory supercomplexes; Mutation, Missense; UQCRC2 (Core2, Core 2); Homozygote; Mitochondrial Encephalomyopathies; mitochondriální encefalomyopatie; Female; Mitochondrial protein quality control; lidé; mitochondrie; Mitochondrial complex III; Mitochondrial Proteins; mitochondriální proteiny; respirační komplex III; homozygot; Mitochondrial dysfunction; kosterní svaly; missense mutace; ženské pohlaví; Electron Transport Complex III; Muscle, Skeletal; fibroblasty; Fibroblasts